Performance evaluation of solar flat plate collector - Nik Mohd Qamarul Shafiq, Nik Ahmad Kamil (2010)
Flat Plate Collectors (FPC) is widely used for domestic hot-water, space heating/drying and for applications requiring fluid temperature less than 100oC. The absorber plate of the FPC transfers solar energy to liquid flowing in the tubes. The flow can takes place due to thermosyphon effect or by forced convection. However, certain energy absorbed by the plate is lost to atmosphere due to higher temperature of the plate. The collector efficiency is dependent on the temperature of the plate which in turn is dependent on the nature of flow of fluid inside the tube, solar insolation, ambient temperature, top loss coefficient, the emissivity of the plate and glass cover, slope, etc. The objective of the present work is to determine the influence of the emissivity of the absorber surface, ambient temperature, spacing between the glass cover and the absorber surface on efficiency of flat plate collector. The influence of operating parameters on flat plate collector is numerical studied. Methods to reduce the losses and compare with the performance of evacuated tube collector (ETC) are proposed by using FORTRAN software. Related equations from previous researcher have been included in the FORTRAN coding the get the data. The influence of the emissivity of the absorber surface, ambient temperature spacing between absorber plate and the glass cover on convection heat transfer coefficient, the overall top loss coefficient are theoretically estimated. The overall top loss coefficient on the flat plate collector is also theoretically determined. It can be observed that the top loss coefficient for the flat plate collector where is between 2.59 Wm-2K-1 until 3.87 Wm-2K-1 while for the evacuated tube collector is 0.7 Wm-2K-1 until 1.04 Wm-2K-1, when the plate temperature is 300K until 350K.